Quantitative effects of vadose zone thickness on delayed recharge of groundwater for an irrigation district in an arid area of Northwest China - Feilong Jie; Liangjun Fei; Shan Li; Kun Hao; Lihua Liu; Jie Li; Nian Liu (Journal of Hydrology: Regional Studies, 2022)
Study region: Jingdian Irrigation District, Northwest China. Study focus: In arid regions, there is a significant lag in groundwater recharge due to the large thickness of vadose zone. For areas with insufficient hydrogeological data, it is quite difficult to calculate the delayed recharge of groundwater. An improved transfer function (ITF) is established based on the instantaneous unit hydrograph of the vadose zone for areas lacking hydro geological data and is then used for calculation of the delayed recharge of groundwater. New hydrological insights for the region: The thickness of the vadose zone is an important factor affecting the delayed recharge of groundwater. When the depth of groundwater is less than 50 m, there is a linear positive correlation between the thickness of the vadose zone and the lag time. For ITF parameters n and k, the number of linear reservoirs n increases as the thickness of the vadose zone increases, and the 1 m thickness of the vadose zone is equivalent to 0.47 linear reservoirs. The storage ability parameter k increases as groundwater depth increases, with an increased rate of 8.89 and 0.62 day/m when the water-table depth is less than 8 m or greater than 8 m. In this paper, a simple improvement to the calculation method for groundwater recharge is of great reference significance for calculating groundwater resources for irrigation regions in similar areas.